The Potency of Protein Extracts from Candida albicansas Bioreceptor on Immunosensor for Diagnosis of Candidiasis - Masfufatun .; Noer Kumala; Afaf Baktir (UNEJ e-Proceeding, 2014)
Currently diagnosis of candidiasis still usingthe traditional standard blood culture method. The traditional method were less sensitive andtime consuming. The purpose of this research were to develope the more sensitive immunosensor based method, and to examine the potency of C. albicans protein extract as bioreceptor to  detect  C. albicans and its biofilm in the blood of candidiasis patients.The research methods include: (1) preparation of  digestive gland liquid of snail (Achatina fulica); (2) extraction of protein from C. albicans  through  enzimatis and mechanic methodsand (3) analyzing the protein extract as bioreseptor through immunodot assay.The research results showed that the snail enzymes has protein content 1.35 mg/ml and  specific activity 1.96 unit/mg. The snail enzyme hydrolyzed  the cell wall of C. albicans  with and without sonication, producedplanktonic extracell protein extract (PEP) and biofilmextracell proteinextract (PEB), planktonic intracell protein extract (PIP), and biofilmintracell protein extract (PIB), withprotein content 1.44; 1.29; 1.29 and 1.21 mg/ml respectively. Thebiofilm intracell protein (BIP) showed antigenic property towardantibody anti-Candida (positive control),giving red spot on imunodot assay. Immunodot assay can distinguishnegative control serum (health man) and positive Candidiasis control by using antigen 1 mg/ml and50ml serum. Keywords: C. albicans, candidiasis, biofilm, immunodot assay